Kepastian Hukum Pemberian Izin Pemanggilan Notaris Oleh Aparat Penegak Hukum - Aquino Noval; Dhody Ar. Widjajaatmadja; Refki Ridwan (Postgraduate of Jayabaya University, 2018)
Notary is a public official based on the law, therefore in carrying out his / her position the Notary has privileges. Article 66 paragraph (1) letter b of the Law on the Position of Notary states that for the benefit of the judicial process, investigators, public prosecutors, or judges with the approval of the Notary Honorary Council are authorized to: summon the Notary to be present at the examination relating to the Notary Deed or Protocol that is in the Notary’s custody. And confirmed by the Regulation of the Minister of Law and Human Rights Number 7 of 2016 concerning the Notary Honorary Council. However, the regulation does not state how many times the Notary Honorary Council can be summoned by the Notary Honorary Council, resulting in legal uncertainty because in some cases there have been repeated summons of Notaries by the Notary Honorary Council where the results of the Notary Honorary Council’s decisions are inconsistent. This research is a normative juridical research. The data used is secondary data consisting of primary legal materials and secondary legal materials. Data analysis is carried out using qualitative juridical analysis methods. From the results of the research, it can be obtained that the legal certainty of the decision of the Regional Notary Honorary Council regarding the granting of permission to summon Notaries by law enforcement officials can be created if in making this decision, the Regional Notary Honorary Council is consistent and in making the decision must be in accordance with the regulations of the minister of law and human rights Number 7 of 2016.